INTERFERENSI FONOLOGIS PENUTUR BAHASA MELAYU KUPANG KE DALAM BAHASA INDONESIA DI KOTA KUPANG - Rafael, Agnes Maria Diana (Universitas Muhammadiyah Surakarta, 2019)
The aims of this study is to identify and describe phonological forms of BMK into BI and the factors that cause the interference of BMK into BI. In accordance with the characteristics studied, this research is included in descriptive-qualitative research. The population in this study were 50 urban residents aged 17-45 years who had different educational and occupational backgrounds. Primary data in this study was obtained by observing the events in formal places. Meanwhile the secondary data was obtained through interviews with the informants. The results of the study found that there was a disturbance of zero affliction, apokop and syncope in formal speech. The data is also proved the diphthong sound [aw] is changed to be a mono single vowel, medium (top) round, semi closed sound [o]. Furthermore, the factors that cause the BMK interference into BI are the bilingual factor, the prestige factor and the nativization process (BMK is a creole language).